2014
DOI: 10.1128/aac.02427-14
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Cellular c-Jun N-Terminal Protein Kinase and NF-κB Activation by Berberine May Result in Inhibition of Herpes Simplex Virus Replication

Abstract: bBerberine is a quaternary ammonium salt from the protoberberine group of isoquinoline alkaloids. Some reports show that berberine exhibits anti-inflammatory, antitumor, and antiviral properties by modulating multiple cellular signaling pathways, including p53, nuclear factor B (NF-B), and mitogen-activated protein kinase. In the present study, we investigated the antiviral effect of berberine against herpes simplex virus (HSV) infection. Current antiherpes medicines such as acyclovir can lessen the recurring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 62 publications
0
68
0
Order By: Relevance
“…BBR has been reported to have multi pharmacological effects such as antibacterial effect [19], hypotensive effect [33], and antiviral activity [21, 22]. It has been reported that BBR could regulate signaling pathway in vitro, such as, EGFR/MEK/ERK signaling pathway [23], AMPK/mTOR signaling pathway [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BBR has been reported to have multi pharmacological effects such as antibacterial effect [19], hypotensive effect [33], and antiviral activity [21, 22]. It has been reported that BBR could regulate signaling pathway in vitro, such as, EGFR/MEK/ERK signaling pathway [23], AMPK/mTOR signaling pathway [24].…”
Section: Discussionmentioning
confidence: 99%
“…1a), an isoquinoline alkaloid isolated from Berberis vulgaris L. , has been reported to have multi pharmacological effects such as antidiarrheal effect [18], antibacterial effect [19], hypotensive effect [20], and antiviral activity [21, 22]. Most of these pharmacological effects is known to be associated with the mechanisms that BBR regulates signaling pathway in vitro, such as, EGFR/MEK/ERK signaling pathway [23], NF-κB pathway [22], AMPK/mTOR signaling pathway [24]. In addition, Deng et al demonstrated that BBR attenuates autophagy in adipocytes by targeting BECN1 [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have demonstrated that berberine impedes virus repli- cation by modifying the cellular signaling environment (40)(41)(42). To pinpoint the pathways that are altered by berberine in CHIKV infection, we employed a human phosphokinase array that allows for detection of changes in the relative phosphorylation levels of a panel of different cellular kinases and their substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past several decades, numerous biological effects of berberine have been discovered, such as its anticancer [6], antilipogenic and hypoglycemic [7], neuroprotective [8], and antimicrobial effects against fungal pathogens [9] and bacterial pathogens [10]. In addition, berberine has been shown to exert antiviral effects against viruses such as herpes simplex virus, human cytomegalovirus, and influenza A virus [11][12][13].…”
Section: Introductionmentioning
confidence: 98%